Mediating effect of new media users’ satisfaction on the relationship between value perception and brand loyalty - Ruan, Qijie; Wan Abas, Wan Anita; Hassan, Abd Rauf (Human Resources Management Academic Research Society (HRMARS), 2024)
Abstract With the rapid development of new media, its potential mediating role between consumer value perception and brand loyalty has attracted the attention of scholars. Therefore, this paper aims to explore the mediating effect of new media user satisfaction between value perception and brand loyalty. Starting from the perspective of literature review, this study deeply investigates the concepts, theories and research controversies of new media, user satisfaction, value perception and brand loyalty. A large number of studies have shown that these four factors have multiple interactions and influences, and the use of new media has a significant impact on users' value perception and brand loyalty, which is embodied in many aspects and is also affected by user satisfaction. Based on the results of literature review, we have constructed a conceptual framework as a guiding principle for the research on the mediating effect of new media user satisfaction between value perception and brand loyalty. The conceptual framework clarifies the relationship between each factor and provides a basis for the design of subsequent empirical research methods. Further, we use quantitative research methods, select a large number of new media users as research objects, and apply structural equation models for data analysis. The data results show that the satisfaction of new media users indeed plays a significant mediating role between value perception and brand loyalty, which not only confirms our conceptual framework, but also provides empirical evidence for the operation of new media and brand marketing. This result's possible theoretical basis and application scenarios, including the application of new media, strategies for maintaining user satisfaction, possible ways to enhance brand loyalty, etc., are fully discussed, hoping to provide references for related enterprises and scholars. The conclusion summarizes the main research results of the paper, pointing out that new media user satisfaction plays an important mediating role between value perception and brand loyalty, and proposes future research directions. Future research should pay more attention to other possible influencing factors, as well as the differences of this mediating effect in different new media environments. To sum up, this paper explores the mediating effect of new media user satisfaction between perceived value and brand loyalty from both theoretical and empirical perspectives, providing a new angle to understand the relationship between new media, user satisfaction, value perception and brand loyalty, and providing valuable theoretical and practical references for new media operation and brand management.